A Systematic Review Experimental And Numerical Studies On The Mechanical Properties Of Cfs Section At Elevated Temperature And After Cooling Down - Salim, Muhamad Shazarul (Universiti Sains Malaysia, 2021)
In recent years, the fire safety of cold-formed steel (CFS) buildings has gained more attention and cold-formed steel (CFS) members have expanded their use in residential, commercial and industrial buildings. It is important to review the mechanical properties of the cold-formed steel at elevated temperature and after cooling down. This study is purposely to conduct a systematic literature review to identify gaps in current knowledge of mechanical properties of cold-formed steel when subjected to elevated temperature and cooling down process, making it more usable for both practitioners and researchers. There are four phase of systematic literature review protocol, i.e., formulate review question, define searching strategy, define data extraction and define data synthesis. The objective of this study is to examine experimental and numerical investigations conducted in examining the mechanical properties of cold-formed steel (CFS) sections at elevated temperatures and after cooling down. It also discusses the influence of elevated temperatures and cooling down on mechanical properties of cold-formed steel (CFS) section. Based on the finding observed from experimental investigation, steady-state test is the most popular approach now employed for the mechanical properties of steels at elevated temperature while for numerical investigations, predictive equations are commonly presented in numerical studies to determine the mechanical properties of cold-formed steel (CFS). Then, due to the high capacity to handle non-linear issues, ABAQUS was preferably for numerical investigation. According to findings, it has been found that different type of CFS grade and different type of CFS section affect the mechanical properties of CFS such as yield strength, ultimate strength, elastic modulus and ductility at different temperature.